2019
DOI: 10.1177/2158244019854646
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Biofeedback Response to Art Therapy? A Technology-Assisted Approach for Reducing Anxiety and Stress in College Students

Abstract: College students are exposed to daily stressors throughout their academic careers, which can have lasting consequences to their health and well-being. Mindfulness practices, art therapy, and the simple act of manipulating clay have independently demonstrated positive effects on stress and anxiety, but there is little research on the feasibility of incorporating these into an online resource for students to proactively address their mental health. In this pilot study, full-time university students (N = 15) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…It is a painting form closest to the Chinese people's aesthetic and cultural ideals. Being under chronic stress may have a seriously negative impact on a person's overall health (Beerse et al, 2019). Whether for an artist or a beginner, appreciation for and creation of Chinese flower and bird paintings can bring lasting euphoria and physical fitness, which are conducive to fostering a strong and optimistic attitude.…”
Section: Introductionmentioning
confidence: 99%
“…It is a painting form closest to the Chinese people's aesthetic and cultural ideals. Being under chronic stress may have a seriously negative impact on a person's overall health (Beerse et al, 2019). Whether for an artist or a beginner, appreciation for and creation of Chinese flower and bird paintings can bring lasting euphoria and physical fitness, which are conducive to fostering a strong and optimistic attitude.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the study suggest that this MBAT intervention not only effectively reduces anxiety and stress, but the delivery strategy lends itself to several valuable clinical applications. Supporting the limited findings of the original pilot study (Beerse, Van Lith, & Stanwood, ), students in the MBAT group reported significant decreases in their symptoms of anxiety and perceived stress, while students in the NCT group did not. Salivary cortisol concentrations significantly decreased pre‐ to post‐intervention for both groups, but indications of these findings are ultimately inconclusive.…”
Section: Discussionmentioning
confidence: 53%
“…(b) Will the MBAT group experience greater decreases in levels of anxiety and perceived stress? Based on preliminary data from a previous pilot study (Beerse, Van Lith, & Stanwood, ), the researchers hypothesized that statistical analysis of outcome measures would affirm the research questions.…”
Section: Methodsmentioning
confidence: 99%
“…University students have to go through every day stressors all through their scholarly careers which can have enduring results to their health and well-being. A study conducted on university students in Florida state university USA revealed that art therapy helped in the significant decrease of the symptoms of anxiety and not in the level of stress (Beerse et al 2019 ). Comes about of the ponder shown that from pre-test to post-test measures, it was evidenced that this therapy was found effective for the decline in depression, anxiety, stress and increase in psychological well-being of the sample of the university students.…”
Section: Discussionmentioning
confidence: 99%